Hematopoietic stem cell transplantation in children with chronic granulomatous disease: the Spanish experience - Alonso García, Laura; Bueno Sánchez, David; Fernández Navarro, Jose Maria; Regueiro Garcia, Alexandra; Blanquer Blanquer, Miguel; Benitez Carabante, Maria Isabel; Mozo del Castillo, Yasmina; Fuster Soler, Jose Luis; Uria Oficialdegui, Maria Luz; Sisinni, Luisa; Perez Martinez, Antonio; Diaz de Heredia Rubio, Cristina (Frontiers in Immunology, 2024)
Hematopoietic stem cell transplantation (HCT) can cure chronic granulomatous disease (CGD). However, transplant-associated morbidity or mortality may occur, and it is still controversial which patients benefit from this procedure. The aim of this retrospective study was to evaluate the outcome of pediatric patients who received HCT in one of the Spanish pediatric transplant units. Thirty children with a median age of 6.9 years (range 0.6-12.7) were evaluated: 7 patients received a transplant from a sibling donor (MSD), 22 received a transplant from an unrelated donor (UD), and 1 received a haploidentical transplant. The majority of the patients received reduced intensity conditioning regimens based on either busulfan plus fludarabine or treosulfan.Relevant post-HCT complications were: (i) graft failure (GF), with a global incidence of 28.26% (CI:15.15-48.88), 11.1% in patients with MSD (1.64-56.70), and 37.08% in unrelated donors (19.33-63.17); (ii) chronic graft vs host disease (GVHD), with an incidence of 20.5% (8.9-43.2), 11.1% in patients with ). Post-HCT infections were usually manegeable but 2 episodes of pulmonary aspergillosis were diagnosed in the context of graft rejection. ). There were no statistically significant differences among donor types.HCT in patients with CGD is a complex procedure with significant morbidity and mortality, especially in patients that receive grafts from unrelated donors. These factors need to be considered in the decision-making process and when discussing conditioning and GVHD prophylaxis.